MULTI-RESPONSES OPTIMIZATION FOR QUALITY OF WC-12Co COATING BASED ON MRWSN METHOD - Nguyen Thanh Phu; Dinh Van Chien; Dao Duy Trung; Le Van Thoai; Doan Thanh Hoa (Journal of Applied Science and Technology, 2019)
In this study, the MRWSN (Multiple Regression-Based Weighted Signal-to-Noise Ratio) multiresponses optimization method is used to determine spray parameters for improving the WC-12Co coating quality by HVOF (High Velocity Oxygen Fuel) spraying. The hardness, adhesion, and porosity of the coating are evalueted through the influence of spray parameters including powder feed rate (A), spraying distance(B), and the ratio of oxygen/propane (C). With the optimal spray paramters of A = 32gam/min, B = 0.35m, and C = 5, the hardness, adhesion strength and porosity of the obtained coating are 1336.2 HV, 64.7Mpa, 1.83%, respectively. Comparing with results single-response optimization method based on Taguchi method, it is shown that proerties of the coating are significantly improved. The verification experiment with optimalspray parameters is performed; the obtained results demonstrate the reliability and high efficiency of the MRWSN method. Therefore, one can say that present MRWSN method has sucessfully applied to multiresponses optimization for spay HVOF process